Relevance of hepatic lipase to the metabolism of triacylglycerol-rich lipoproteins. (1st October 2003) - Zambon, A.; Bertocco, S.; Vitturi, N.; Polentarutti, V.; Vianello, D.; Crepaldi, G.
Abstract : HL (hepatic lipase) is a glycoprotein that is synthesized and secreted by the liver, and which binds to heparan sulphate proteoglycans on the surface of sinusoidal endothelial cells and on the external surface of parenchymal cells in the space of Disse. HL catalyses the hydrolysis of triacylglycerols and phospholipids in different lipoproteins, contributing to the remodelling of VLDL (very-low-density lipoprotein) remnants, as well as IDL, LDL and HDL (intermediate-, low- and high-density lipoprotein respectively). HL deficiency in humans is associated with diminished conversion of VLDL remnants into IDL and a near-complete absence of IDL-to-LDL conversion. Remnant lipoproteins and IDL are major determinants of coronary artery disease risk, and accumulation of these lipoproteins in the presence of low HL activity might lead to increased atherosclerosis. In addition to and independently of its lipolytic activity, HL participates as a ligand in promoting the hepatic uptake of remnants and IDL particles, and the latter may represent an additional mechanism linking low HL levels to plasma accumulation of these atherogenic lipoproteins. On the other hand, high HL activity may also result in an increased atherosclerotic risk by promoting the formation of atherogenic small, dense LDL particles. Finally, HL is also synthesized by human macrophages, suggesting that, at the arterial wall site, HL may also contribute locally to promote atherosclerosis by enhancing the formation and retention in the subendothelial space of the arterial wall of VLDL remnants, IDL and small, dense LDL. In conclusion, by interfering with the metabolism of apolipoprotein B100-containing lipoproteins, HL may have pro- as well as anti-atherogenic effects. The anti- or pro-atherogenic role of HL is likely to be modulated by the concurrent presence of other lipid abnormalities (i.e. LDL-cholesterol levels), as well as by the genetic regulation of other enzymes involved in lipoprotein metabolism.